Pemikiran Fiqh Lestari dan Pemakaiannya ke atas Isu-Isu Terpilih dalam Hal Ehwal Mu’allaf di Malaysia: Sustainable Fiqh Thought and its Application on Selected Issues in Mu’allaf Affair in Malaysia - Abdullah, Atikullah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
It is very crucial to ensure that Islamic fiqh continues to be dynamic and relevant to the realities of the contemporary societies. This will result in the sustainabilty of fiqh and make it acceptable within the societies main stream. Towards this end, all the existing qualities of fiqh as shown to us by the fiqhi scholars in the past need to be highlighted and brought forward. The fiqh with the sustainability qualities or sustainable fiqh as mentioned above need to be put into practice as the guide line in evaluating some related contemporary issues. In mu’allaf affair for example, there are issues need to be adressed properly and wisely using sustainable fiqh principles to ensure the interest of all are well protected and the Islamic fiqh is always trusted.